Gold nanoparticle-based lateral flow immunoassay for the rapid detection of flumetralin in orange. Issue 16 (15th July 2022) - Xu, Xinxin; Lin, Lu; Kuang, Hua; Liu, Liqiang; Xu, Liguang; Xu, Chuanlai
Abstract : A sensitive monoclonal antibody (mAb) against flumetralin was produced and a gold nanoparticle-based lateral flow immunoassay (LFIA) strip was developed for screening flumetralin in orange. Abstract : Residues of flumetralin, a dinitroaniline herbicide, in foods pose a health risk to humans. In this study, we produced a sensitive monoclonal antibody (mAb) against flumetralin and developed a gold nanoparticle-based lateral flow immunoassay (LFIA) strip for screening flumetralin in orange. The subtype of mAb 3F5 was IgG1 and had a half-maximal inhibitory concentration of 9.43 ng mL −1 . The cross-reactivity assay indicated that mAb had good specificity. The LFIA strip had a visual limit of detection of 200 ng g −1 in orange. We obtained results with the naked eye within 15 min. The calculated LOD of the strip in orange was 33.26 ng g −1, with a linear detection of 80.72–1672.10 ng g −1 . The strip had recovery rates ranging from 98.4% to 110.1%. Therefore, our developed method is an effective and reliable tool for the rapid detection of flumetralin in orange.